Study on Internal Communication among Groupthink of Employee at Puri Asih Group Clinic Karawang - Paojan, Ahmad; Zulaikha, Zulaikha; Widiarto, Didik Sugeng; Maella, Nurannafi Farni Syam; Farida, Farida (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Good internal communication is absolutely necessary for companies to have a cooperative and efficient workplace. With an eye toward the phenomena of groupthink among staff, this study looks at the internal communication dynamics of the Puri Asih Group Clinic in Karawang, Indonesia. Based on the theoretical concept of groupthink, which holds that a very cohesive group may value agreement over critical thought, therefore producing less than ideal decision-making. Examining relevant literature helps one to understand the elements causing groupthink as well as the ways in which companies could reduce its negative consequences. As Robert K. Yin outlines, the study used a case study methodology. Data were gathered via in-depth employee interviews, clinic operations observation, and document analysis of relevant materials. Using the case study approach helped one to fully understand the dynamics of internal communication inside the Puri Asih Group Clinic. The findings show that the Puri Asih Group Clinic had groupthink traits including a strong focus on maintaining peace, a high degree of cohesiveness, and insulating from outside viewpoints. These elements led to a lack of critical assessment of decisions and a resistance to question the status quo, therefore affecting the general performance and flexibility of the clinic. The study provides insightful analysis for the Puri Asih Group Clinic and such medical facilities in overcoming groupthink's challenges. The outcomes show the need of encouraging critical thinking, a more inclusive and open communication environment, and policies that support informed decision-making and many points of view. The implications of this research can guide the creation of efficient internal communication plans and organizing techniques meant to raise organizational resilience and employee involvement.